Analisis Sifat Fisik dan Kompresibilitas Nanopowder Zinc Oxide (ZnO) sebagai Alternatif Material Amalgam - Qosim, Nanang; Murdanto, Putut; Puspitasari, Poppy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Severe effects of the mercury use on health as an amalgam material have required an alternative material in order to eliminate it from amalgam composition. This research was conducted to analyze the physical properties and compressibility of ZnO nanopowder as an alternative amalgam material. The physical properties including morphology, dimensions, and the atomic ratio were analyzed by SEM, XRD-XRF and EDX. Further, the compressibility was conducted by using hydraulic press machine. The results showed that ZnO has particle size of 14.34 nm with morphology classified as nanorods. In the compressibility test, both the variation of compression loadings and holding time have brought an effect on the significant increase of ZnO nanopowder density.